An assessment of the difficulties encountered by working students - Barrera, Joselito Leocario, Jr
This study aims to asses the difficulties encountered by working students in coping with their academics. It identifies five factors - financial, academic, time, personal and environment - which their interplay affects the academic performance of working students. It reveals which among these factors caused the more burden to them. The study was conducted by distributing questionnaires to working students in second to fifth year levels and in all courses of the College of Management,UP in the Visayas, Iloilo City. Only Students who are working under business establishments for remuneration are the subjects of the study. It excludes students who are working under the Student Assistantship Program of the university and students who are working as Korean english tutors. The data collected from questionnaires were supplemented by interviews with key respondents and library research. It was found out that the students are not compelled financially to work, and their job does not reduced contact with their teacher. But part-time employment reduces their time for studying daily and its demand come n conflict with class expectations. Furthermore, the problems that jobs bring to the students encroach on their class participation. To sum up, employment does pose difficulties to students in coping with their academic demands.